2022
DOI: 10.3390/ph15010087
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Fractionation of Bioactives from Dipsacus fullonum L. Leaves and Evaluation of Their Anti-Borrelia Activity

Abstract: Lyme disease (LD) is a tick-borne bacterial disease that is caused by Borrelia burgdorferi. Although acute LD is treated with antibiotics, it can develop into relapsing chronic form caused by latent forms of B. burgdorferi. This leads to the search for phytochemicals against resistant LD. Therefore, this study aimed to evaluate the activity of Dipsacus fullonum L. leaves extract (DE) and its fractions against stationary phase B. burgdorferi in vitro. DE showed high activity against stationary phase B. burgdorf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…Plants are a natural source of active compounds, phytochemicals, many of which with favourable bioactivity for humans. Analytical investigation allows for the determination of the phytochemical composition and confirmation of specific therapeutic properties of the plants already acknowledged for their potential by ethnomedicine [ 1 , 2 , 3 , 4 , 5 ]. The Galium L. genus, comprising about 667 species found worldwide, over a third of which can be found in Europe, includes several species that have been used in traditional medicine to alleviate a variety of ailments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are a natural source of active compounds, phytochemicals, many of which with favourable bioactivity for humans. Analytical investigation allows for the determination of the phytochemical composition and confirmation of specific therapeutic properties of the plants already acknowledged for their potential by ethnomedicine [ 1 , 2 , 3 , 4 , 5 ]. The Galium L. genus, comprising about 667 species found worldwide, over a third of which can be found in Europe, includes several species that have been used in traditional medicine to alleviate a variety of ailments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another species of Dipsacus is D. fullonum L., commonly known as teasel or wild teasel [33,34]. Traditionally, D. fullonum has been used to treat Lyme disease [35] and eye infections in cattle [36].…”
Section: Dipsacus Sppmentioning
confidence: 99%
“…Some representatives of Dipsacus and Scabiosa biosynthesize chemical compounds of various classes, mainly triterpenoid derivatives (Table 2) [5][6][7]12,21,22,27,40,48,49,51,65,66,81,82,[88][89][90][91][92][93][94][95][96], which possess a variety of bioactivities. In addition, iridoids [6,7,13,22,27,33,34,65,66,75,78,84,89,[92][93][94][95][96][97][98][99][100] (Table 3), phenolic acids [6,24,27,29,…”
Section: Chemical Constituents Of Dipsacus and Scabiosa Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the potential impacts of dietary proteins on the reduction of BDs was recently highlighted [ 23 ] and supported by two systematic reviews and meta-analyses studies conducted independently, which collectively reported that dietary protein intake improved femoral neck and total hip BMD, showed improvements on the lumbar spine, and significantly reduced cases of hip fractures [ 24 , 25 ]. In previous reviews, the pro-osteoanabolic and anti-osteocatabolic properties of extracts from different plant species were thoroughly discussed [ 26 , 27 , 28 , 29 ], motivating several new studies on the application of herbal materials in halting bone resorption in vitro and in vivo [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In this review, we aim to discuss the cellular and molecular mechanisms behind the health-promoting benefits of selected plant-derived and purely characterized NPs.…”
Section: Introductionmentioning
confidence: 99%